2014
DOI: 10.36283/pjr.zu.3.1/006
|View full text |Cite
|
Sign up to set email alerts
|

Postural Awareness in School Going Students and Teachers

Abstract: OBJECTIVES To determine the awareness level of good body posture in school going students and teachers of different academic places and compare the level of awareness between students and teachers. STUDY DESIGN A cross sectional study was conducted during January 2013 to April 2013. STUDY SETTINGS & PARTICIPANTS Research data was collected from different schools of Karachi. One hundred and thirty two participants including both school going students and teachers were participated in this study. The student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The source of information about the correct sitting posture was conveyed by parents (81.5%) and teachers (34.7%) to the participants; however internet (1.7%) and peer group (1%) were not significant sources of information. A previous study done by Yasmeen et al 15 found that 70% of teachers used a proper back support while sitting and 75% of teachers sat with equal distribution of weight on both sides in contrast to students whereas 47.3% sat with exerting body weight more on one side this indicates that teachers had good information about correct sitting habits than the students.…”
Section: Discussionmentioning
confidence: 88%
“…The source of information about the correct sitting posture was conveyed by parents (81.5%) and teachers (34.7%) to the participants; however internet (1.7%) and peer group (1%) were not significant sources of information. A previous study done by Yasmeen et al 15 found that 70% of teachers used a proper back support while sitting and 75% of teachers sat with equal distribution of weight on both sides in contrast to students whereas 47.3% sat with exerting body weight more on one side this indicates that teachers had good information about correct sitting habits than the students.…”
Section: Discussionmentioning
confidence: 88%